SPECTROPHOTOMETRIC ESTIMATION OF CILNIDIPINE IN BULK AND PHARMACEUTICAL DOSAGE FORM USING N-(1-NAPHTHYL) ETHYLENE DIAMINE DIHYDROCHLORIDE - Kokilambigai, K. S.; Lakshmi, K. S.; Kumar, Amlesh; Chandrayan, Govind; Satyam, Kumar; Singh, Mantosh Kumar (International Journal of Pharmacy and Pharmaceutical Sciences, 2014)
Objective: To develop a new, simple and sensitive visible spectrophotometric method for the estimation of Cilnidipine [CIL] in bulk and tablet dosage forms. Methods: The visible spectrophotometric method was based on the color reaction of CIL with N-(1-Naphthyl) ethylene diamine dihydrochloride reagent [it is stable for 20 min] to form a purple coloured chromophore that has an absorption maxima at 554 nm. The method was validated as per ICH guidelines. Results: Beer's law was obeyed over the concentration range of 16-24 Î¼g/mL for Cilnidipine. Limit of detection [LOD] and limit of quantification [LOQ] are 0.4365 and 1.3228 respectively. The average recovery was found to be 100.43% w/w. Conclusion: The method developed is precise, linear and accurate. Satisfactory results were obtained from validation of the method. Hence the proposed method is suitable in quality control of estimation Cilnidipine bulk and pharmaceutical dosage forms. Â 